A new species of anguilliform catfish (Actinopterygii: Siluriformes: Bagridae) from Bangladesh and northeastern India - Ng, Heok Hee; Ferraris, Carl J. Jr (Zootaxa, 2016)
We describe Olyra praestigiosa, a new anguilliform bagrid catfish, from the Brahmaputra River drainage in Bangladesh and northeastern India. The new species differs from congeners in having the following unique combination of characters: interorbital distance 30–37% HL; body depth at anus 6–9% SL; length of adipose-fin base 99–16% SL; adipose fin separate from upper principal caudal-fin rays; post-adipose distance 15–18% SL; 17–22 anal-fin rays; caudal peduncle length 14–19% SL; and caudal peduncle depth 6–8% SL.